Choroidal thickness measurement in healthy Japanese subjects by three-dimensional high-penetration optical coherence tomography - Agawa, Tetsuya; Miura, Masahiro; Ikuno, Yasuhi; Makita, Shuichi; Fabritius, Tapio; Iwasaki, Takuya; Goto, Hiroshi; Nishida, Kohji; Yasuno, Yoshiaki (Graefe's archive for clinical and experimental ophthalmology, 2011)
Background We performed retinal and choroidal thickness mapping by three-dimensional high-penetration optical coherence tomography (OCT) and evaluated the choroidal thickness distribution throughout the macula in healthy eyes. Methods Forty-three eyes of 43 healthy Japanese volunteers were evaluated by 1060-nm swept-source OCT. The eyes were scanned with a three-dimensional raster scanning protocol, and the mean retinal and choroidal thicknesses of the posterior sectors were obtained. The sectors were defined by the Early Treatment Diabetic Study (ETDRS) layout. These data were compared by age (23–56 years), spherical equivalent refractive error (between +0.9 D and −10.3 D), and axial length (22.9–27.6 mm). Results The mean retinal and choroidal thicknesses of the ETDRS area were 284 ± 14 μm and 348 ± 63 μm respectively. The mean regional choroidal thicknesses in the nasal inner macula and nasal outer macula were significantly smaller than those in all other sectors. The mean regional choroidal thickness in most sectors showed a significant negative correlation with axial length and a significant positive correlation with refractive error. In eyes with a long axial length (>25.0 mm), the mean regional choroidal thickness of five sectors showed a significant negative correlation with age. The coefficient of variation of choroidal thickness between sectors showed a significant negative correlation with axial length, and a positive correlation with refractive error. The mean retinal thickness in each sector was not significantly correlated with the mean choroidal thickness, age, axial length, or refractive error. Conclusions The choroidal thickness map showed a distribution entirely different from the retinal thickness map. Choroidal thickness varies significantly with location, axial length, refractive error, and age. These variations should be considered when evaluating choroidal thickness.